2016
DOI: 10.1021/acs.jpcb.6b09215
|View full text |Cite
|
Sign up to set email alerts
|

Osmolyte Effects on the Growth of Amyloid Fibrils

Abstract: Understanding the role of naturally occurring protective osmolytes, such as trimethylamine N-oxide (TMAO), in the growth of amyloid fibrils implicated in neurodegenerative diseases is important to prevent fibril growth. The effect of TMAO on the growth of amyloid fibrils formed by the Sup35 prion peptide NNQQNY is studied using molecular dynamics simulations. The free-energy surface for the growth of the protofibril shows three major basins, corresponding to the free state where the peptide is in solution, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 106 publications
(178 reference statements)
1
13
0
Order By: Relevance
“…The process of amyloidosis is caused by the misfolding and aggregation of proteins, and it leads to many known diseases such as Alzheimer’s disease (AD), Parkinson’s disease, type-2 diabetes, Huntington’s disease, and spongiform encephalopathy. Alzheimer’s is the most common form of neurodegenerative disease in which amyloid fibril plaques have been found to be formed in the brains of concerned patients. The fibril plaques mainly consist of highly ordered β-sheet-rich structures in which the β sheets are arranged perpendicularly to the fibril axis. ,,, In AD, amyloid-β (Aβ) peptides (mainly Aβ(1–40) and Aβ(1–42)), which are produced through endoproteolysis of the β-amyloid precursor protein (βAPP) by β- and γ-secretase sequentially, aggregate and get deposited in the human brain, leading to the death of active brain cells. ,, Of the two forms, Aβ(1–42) has been found to be neurologically more toxic than Aβ(1–40). , It has been reported that low-molecular-weight soluble prefibrillar oligomers and protofibrils are more responsible for neurotoxicity. There have been both experimental and theoretical studies which have looked at a variety of nanoparticles, small peptides, and organic molecules for the prevention of AD. Although the mechanism of amyloid formation is not yet fully resolved, , various experimental studies have proposed that the initial random coil or α-helical structure of Aβ(1–42) monomers first get converted to β-sheet structures which then assemble to form Aβ aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…The process of amyloidosis is caused by the misfolding and aggregation of proteins, and it leads to many known diseases such as Alzheimer’s disease (AD), Parkinson’s disease, type-2 diabetes, Huntington’s disease, and spongiform encephalopathy. Alzheimer’s is the most common form of neurodegenerative disease in which amyloid fibril plaques have been found to be formed in the brains of concerned patients. The fibril plaques mainly consist of highly ordered β-sheet-rich structures in which the β sheets are arranged perpendicularly to the fibril axis. ,,, In AD, amyloid-β (Aβ) peptides (mainly Aβ(1–40) and Aβ(1–42)), which are produced through endoproteolysis of the β-amyloid precursor protein (βAPP) by β- and γ-secretase sequentially, aggregate and get deposited in the human brain, leading to the death of active brain cells. ,, Of the two forms, Aβ(1–42) has been found to be neurologically more toxic than Aβ(1–40). , It has been reported that low-molecular-weight soluble prefibrillar oligomers and protofibrils are more responsible for neurotoxicity. There have been both experimental and theoretical studies which have looked at a variety of nanoparticles, small peptides, and organic molecules for the prevention of AD. Although the mechanism of amyloid formation is not yet fully resolved, , various experimental studies have proposed that the initial random coil or α-helical structure of Aβ(1–42) monomers first get converted to β-sheet structures which then assemble to form Aβ aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…Another group studied the fibrillation process in the presence of TMAO of the peptide NNQQNY (of Sup35 prion) by molecular dynamics simulation (MDS) method [110]. When the free surface energy of the formation of protofibril was observed, it showed three main basins which corresponded to the time when peptide was in solution, known as free state, the time when the peptide in the solution was interacting with the surface of the protofibril, known as the docked state and the last stage when the peptide gets tightly bound to the protofibril and thus becoming a part of fibril known as locked state [110]. When these studies were performed in the presence of TMAO, it was found that this osmolyte stabilized the locked state and thus acting as an aid in the process of aggregation [110].…”
Section: Osmolytes and Process Of Amyloidosismentioning
confidence: 99%
“…When the free surface energy of the formation of protofibril was observed, it showed three main basins which corresponded to the time when peptide was in solution, known as free state, the time when the peptide in the solution was interacting with the surface of the protofibril, known as the docked state and the last stage when the peptide gets tightly bound to the protofibril and thus becoming a part of fibril known as locked state [110]. When these studies were performed in the presence of TMAO, it was found that this osmolyte stabilized the locked state and thus acting as an aid in the process of aggregation [110]. When the associative reactions of TMAO with each amino acid residue in the protein were studied in detail, it was found that TMAO interacted with each amino acid residue either directly or indirectly, and this was determined by nature of their side chain.…”
Section: Osmolytes and Process Of Amyloidosismentioning
confidence: 99%
See 1 more Smart Citation
“…The rapidly increasing computational power over the years has allowed harnessing MD simulations to delve into the intricacies of biological processes such as protein folding and misfolding, protein denaturation, protein aggregation, membrane dynamics, protein-protein interactions, proteins-nucleic acid interactions, influence of solvent environments, enzymatic processes, effects of biomimetic crowding, etc. [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] . This method is also, capable of complementing experimental measurements over fairly wide time and length scales.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%